MoPE:DS mobile phone enhancement : digital signing - Castro, Paul Alfonso (2007)
Mobile Phone Enhancement: Digital Signatures (MoPE:DS) is based on an existing framework that utilizes Digital Signatures and Access Controls to secure electronic documents in a web environment. [6] This research extends the framework into Java enabled mobile devices, primarily mobile phones. The software architecture developed in this research allows digital signing to be done on mobile phones so that there are minimal computations done on the client. The backend component allows digital signature verification before signatures are stored in the database. Although this research provides a way for securing documents with this framework, we concluded that it is not sufficient and additional security measures must be employed.